2023
DOI: 10.1002/pssa.202300244
|View full text |Cite
|
Sign up to set email alerts
|

All‐Solid Near‐Infrared Light‐Induced Self‐Written Optical Waveguides and Optical Self‐Coupling

Yasunari Kawasaki,
Haruki Otaka,
Tomomi Ota
et al.

Abstract: In recent datacenters, considerable data communication has been performed between servers and storages; therefore, an optical interconnection with a wider band is required. Silicon photonics has attracted attention as a technology that places optical engines closer to switch application‐specific integrated circuits and realizes broadband optical interconnection. To utilize silicon photonics, it is necessary to overcome high‐precision alignment between silicon waveguides and single‐mode fibers (SMFs) having vas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…Y. Kawasaki et al demonstrated NIR-SWW between two SMF-28 fibers at 1310 nm with low coupling losses also measured at a longer wavelength (0.5 dB @1550 nm for a distance of 100 µm) [7]. Finally, P.A.…”
Section: Introductionmentioning
confidence: 98%
“…Y. Kawasaki et al demonstrated NIR-SWW between two SMF-28 fibers at 1310 nm with low coupling losses also measured at a longer wavelength (0.5 dB @1550 nm for a distance of 100 µm) [7]. Finally, P.A.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, bidirectional light irradiation enables automatic optical coupling between two optical fibers, which is called an "optical solder". 9) Further, various extended technologies based on LISW optical waveguides have been demonstrated, [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] and there is a wider range of applications of LISW optical waveguides.…”
mentioning
confidence: 99%